Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - Nugroho, Adi; Indriyatni, Lies; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to determine whether firm size, leverage, and profitability have an effect on firm value. Sampling was carried out using the purposive sampling method, which is a sampling method with certain criteria. The type of research used is quantitative. The results of this study indicate that firm size has a negative and insignificant effect on firm value, leverage has a negative and insignificant effect on firm value, profitability has a positive and significant effect on firm value. Company Size, Leverage, and Profitability together or simultaneously have a significant effect on Firm Value.Keywords: Firm Size, Leverage, Profitability, Firm Value